Pemberdayaan Masyarakat Melalui Pelatihan Digital Marketing - Muh. Jaelani Al-Pansori; Rian Safriadi; Najwa Suhartati; Qitfirul Mauludi; Rina Jannatil Ain; Nurul Iswara Restu; Siti Zaenab (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
In the information era, digital marketing has become an important strategy for the growth of micro, small, and medium enterprises. (UMKM). The purpose of this research is to evaluate how digital marketing training impacts the capabilities of small and medium enterprises (SMEs) in Masbagik Selatan Village, East Lombok. The training intervention activities conducted by KKN students from Hamzanwadi University in collaboration with BDP Lombok were used as the research method. A total of 50 participants, consisting of youth and MSME workers, attended the training focused on product marketing through digital platforms such as social media. The results showed that participants had a better understanding of digital marketing strategies, the potential use of social media, and online marketing affiliate strategies. According to this research, promoting digital marketing has strategic significance in enhancing the economic capacity of rural communities.